LECTURE D’UN EXIL RÉGÉNÉRATEUR - PRADA, Georgeta (Studia Universitatis Babeș-Bolyai Philologia, 2018)
A reading of a regenerating exile. This article shows that migrant literature too can experience the formula of a happy and fulfilled exile. When discussing about the novel Ru by Kim Thuy, we have tried an in-depth approach of the features of alterity and fragility which can eventually give the writer a strong predisposition to redemption, through the saving act of writing. REZUMAT. Lectura unui exil dezexilant. În acest articol, ne propunem să arătăm că scriitura migrantă cunoaşte de asemenea exilul dezexilant. Având ca suport romanul Ru de Kim Thúy, vom studia trăsăturile alterităţii şi ale fragilităţii care pot găsi o cale izbăvitoare prin actul scriiturii. Cuvinte-cheie: alteritate, dimensiune spaţială, fragilitate, grupuri de referinţă, exil, identitate, scriitură migrantă.